DETERMINANT FACTORS AFFECTING STUDENT INTEREST IN CONTINUE EDUCATION TO HIGHER EDUCATION - Suarni Norawati; Zulher Zulher; Arman Arman; Usman Usman (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Higher education is a demand in today's digital era, so there is a need for awareness of the younger generation to explore their potential and abilities to go to college. This study aims to determine the effect of intelligence, attitude, talent, motivation, social environment and non-social environment both partially and simultaneously on the interest of students continue the study. This study uses primary data and secondary data obtained through questionnaires, interviews, observation and documentation. The sample in this study were 163 students from both schools, where the determination of the number of samples was carried out using the slovin formula. The data analysis tool used is multiple linear regression. Based on the research results partially reveal that Intelligence, Attitude, Talent, Motivation, Social Environment have a significant effect and positively on students' interest in continuing their education to tertiary institutions. However, the non-social environmental and attitude have not an effect on students' interest in continuing their education to tertiary institutions. The results of this study also proved that simultaneously the independent variables have a significant effect on students' interest in continuing their education to tertiary institutions. Keywords: Student Interests, Intelligence, Attitude, Talent, Motivation, Social Environment, Non-Social Environment